2023
DOI: 10.1002/agt2.419
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional nanoaggregate‐based system for detection of rheumatoid arthritis via Optoacoustic/NIR‐II fluorescent imaging and therapy via inhibiting JAK‐STAT/NF‐κB/NLRP3 pathways

Junjie Chen,
Longqi Chen,
Zunpan She
et al.

Abstract: Rheumatoid arthritis (RA) is a debilitating autoimmune disease that causes chronic pain and serious complications, presenting a significant challenge to treat. Promising approaches for treating RA involve signaling pathways modulation and targeted therapy. To this end, a multifunctional nanosystem, TPC‐U@HAT, has been designed for RA therapy, featuring multitargeting, dual‐stimuli response, and on‐demand drug release capabilities. TPC‐U@HAT is composed of a probe/prodrug TPC, a JAK1 kinase inhibitor upadacitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The response mechanism is provided in Scheme 1c and d. Vis-H 2 S , with a molecular rotor structure (two symmetric vinyl-coupled indolium moieties), enhanced the probe fluorescence in a high-viscosity environment due to restricted intramolecular rotation inhibiting nonradiative twisted intramolecular charge transfer (TICT 14–16 ). The nucleophilic reaction of the ester with HS − releases QCy7 in an anionic form, and the negative charge is delocalized to form quinone QCy7-a or QCy7-b .…”
Section: Resultsmentioning
confidence: 99%
“…The response mechanism is provided in Scheme 1c and d. Vis-H 2 S , with a molecular rotor structure (two symmetric vinyl-coupled indolium moieties), enhanced the probe fluorescence in a high-viscosity environment due to restricted intramolecular rotation inhibiting nonradiative twisted intramolecular charge transfer (TICT 14–16 ). The nucleophilic reaction of the ester with HS − releases QCy7 in an anionic form, and the negative charge is delocalized to form quinone QCy7-a or QCy7-b .…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation-induced emission (AIE) concept, which was pioneered by the work of Tang and co-workers, has ushered new frontiers in biosensing and imaging. Specifically, the AIE strategy is a valuable approach for tracking protein aggregates, organelles, and enzymes. , In aggregation-induced emission luminogens (AIEgens), the restriction of excited state intramolecular motion in the aggregated state effectively suppresses nonradiative decay, leading to enhanced fluorescence emission. In 2013, our group first reported that replacing the oxygen atom in dicyanomethylene-4 H -pyran (DCM) chromophore (a classical laser dye) with an N -ethyl group, and the obtaining quinoline-malononitrile (QM) exhibited a twisted molecular conformation with typical AIE properties .…”
Section: Inhibition Of Excited State Intramolecular Motion: From “Alw...mentioning
confidence: 99%
“…24 In general, the strategies of structuring organic fluorophores with NIR-II emission consist of expanding π-systems, strengthening structural rigidity, and introducing strong donor and acceptor groups. 23 To date, various organic fluorescence probes, including cyanine dyes, donor−acceptor−donor (D−A−D) AIE structures, 25,26 and BODIPY dyes have been designed and synthesized. 27 However, most of dye molecules exhibit small Stokes shifts (<70 nm), which requires their absorption band to be located in or very near the NIR-II region.…”
Section: Introductionmentioning
confidence: 99%